Resilience and Adaptive Capacity of the Swan Coastal Plain Wetlands - Nanda, Amar V. V.; Beesley, Leah; Locatelli, Luca; Gersonius, Berry; Hipsey, Matthew R.; Ghadouani, Anas (Frontiers in Water, 2021)
An estimated 90% of the Swan Coastal Plain (SCP) wetlands, located in southwestern Australia, have been lost because of infilling or drainage. This loss continues despite the well-known causes, which include nutrient enrichment; the invasion of exotic flora and fauna; loss of fringing vegetation; and altered hydrological regimes caused by groundwater abstraction; urbanization; and a drying climate. Further loss is expected with climate change exacerbating the undesirable ecosystem changes of remaining wetlands. In this study, we consider these wetlands as examples of social-ecological systems (SES) which are characterized by a close interaction of the ecosystem with the social system. We take the theory of resilient SES as a starting point to identify the adaptive capacity and resilience of the wetlands. We argue that resilience provides a useful framework to analyze adaptation processes and to identify appropriate policy responses. We explore incremental adjustments and transformative action and demonstrate that policy responses arise across multiple scales and levels of jurisdiction and institution. By applying the theoretical framework of resilience to the SCP wetlands, we identified (un)desired ecosystem states of wetlands (hydrology and ecology) through different set of policy actions. Our results show that current wetland management is inadequate to maintain the ecosystem’s functioning. We recommend cross-jurisdictional collaboration and the use of conceptual eco-hydrological models to depict gradual ecological change and types of regime shifts (thresholds, hysteresis, and irreversible changes). The different adaption options inform decision-makers to adequately adapt wetland management practices when uncertainty in ecosystem responses exist. Empirical data on how multiple jurisdictions operate and decide could help to further support decision-making. With this research we aim to narrow the science-policy interface which depends on corresponding cross-jurisdictional and institutional responses to coordinate wetland management policies and actions.